Development of an E-commerce Application System for Durian Entrepreneurs in Narathiwat Province, Thailand - Sangkhapan, Surachet; Pradit, Katekaew; Thongjan, Pakarat; Amornsak, Prarak; Totayong, Jaeinyas (Recent Science and Technology, 2024)
This research and development project aims to create an application for managing processed durian products to support B2B2C e-commerce. The objectives are to 1) study relevant data, 2) design the system architecture, and 3) evaluate system efficiency. The sample group consists of the processed durian community in Bukit Subdistrict, Cho-I-Rong District, Narathiwat Province. The development follows the SDLC model, using NextJS with Server-Side Rendering (SSR) for the frontend, Node.js for the backend, and Firestore on Firebase as a NoSQL database. The system comprises seven core modules: member management, product management, order management, payment channels, database management, multi-vendor management, and reporting. Evaluation by two experts and 30 users shows that the system performs excellently, particularly in meeting user requirements ( = 4.67, S.D. = 0.49), system functionality ( = 4.62, S.D. = 0.55), ease of use ( = 4.57, S.D. = 0.49), and data security ( = 4.60, S.D. = 0.56). The research results indicate that this system is efficient and can be implemented in real-world scenarios. It helps connect community products to online markets through social media, increases sales channels, and can potentially aid in controlling product prices and quality in the future.